Société, oikonomia et affects : correspondance et vie conjugale à Venise (fin XVIe-début XVIIe siècle) - Romain Facchini (Genre & Histoire)
Like gender, the study of emotions and feelings offer new research horizons. This article highlights the heuristic value of affects − feelings and emotions − for a social history of Venice in the sixteenth and seventeenth centuries. Drawing on the correspondence and testaments left by a couple who belonged to the Venetian aristocracy (late sixteenth and early seventeenth century). Three angles guide this investigation : firstly, the couple in society ; then the management of goods received and/or inherited. Finally, I will explore the theme of emotions both as an approach and as an object of study that provides a way of understanding the relational construction of the couple and the individual. The significance of individuals in Venetian society opens perspectives on a history of lived material realities to achieve a form of oikonomia.